Process of development investment exemplified by “Development Project” case study - Kucheruk Dmytro (My University, 2007)
A real-estate development lays in obtaining some kind of real property, making improvements. Improvements influence value increasing. The developer may do his business either individually but usually because of risk he/she prefers doing it in partnership (like e.g. limited liability company, limited partnership). Developer fulfills an empty space that exists between construction companies that are in charge of building and companies that are using real estate like offices, warehouses etc. Developer’s success depends on defining the existing need for some kind of the real property and ability to satisfy it accordingly. To do the job well developer has to organize people like architects, engineers, project managers, market consultants, financial analysts in one team. He has to define the goal, which those people have to achieve together. What’s more important developer has to convince the investors that investment is going to be profitable. Why investors are so important? The thing is that core of the real estate development financing is financial leverage. Developer uses investor’s money (debt) to reinvest them with the intent to make better rate of return than the cost of interest. Speaking in terms of “Development Project” I can conclude that development business today is really complicated and risky, but return is worth to get into it. There are a lot of details in development project financial analysis that should be taken care of. The two most important ratios are IRR and NPV telling us about project’s profitability. To compare few projects investor may use profitability index. Financing of different types of project like residential or commercial also requires different approaches. In case of residential project investor needs to obtain construction loan while building commercial space – he should manage two loans (construction and refinancing). It should be said that in fact investors frequently make their decisions based on some predictions. The reason for that is economic situation in Poland; demand is so high that would probably accept everything. Prices are growing constantly (there are first signs of price would stop growing) etc.
Przebieg inwestycji deweloperskiej na przykładzie projektu “Development Project”
Keywords: development investment; development business; real estate